2017
DOI: 10.1111/bph.13740
|View full text |Cite
|
Sign up to set email alerts
|

Broad spectrum efficacy with LY2969822, an oral prodrug of metabotropic glutamate 2/3 receptor agonist LY2934747, in rodent pain models

Abstract: Following oral administration of the prodrug LY2969822, the mGlu receptor agonist LY2934747 was formed and this attenuated pain behaviours across a broad range of preclinical pain models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 73 publications
1
21
0
Order By: Relevance
“…Both 30 and 100 mg/kg KRM-II-8, p.o, significantly increased paw withdrawal thresholds in these rats as did the positive control drug gabapentin (75 mg/kg, p.o.). The time-course for gabapentin was generally as previously reported with a trend for activity at 1 hr (Johnson et al, 2017).…”
Section: Accepted Manuscript Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Both 30 and 100 mg/kg KRM-II-8, p.o, significantly increased paw withdrawal thresholds in these rats as did the positive control drug gabapentin (75 mg/kg, p.o.). The time-course for gabapentin was generally as previously reported with a trend for activity at 1 hr (Johnson et al, 2017).…”
Section: Accepted Manuscript Resultssupporting
confidence: 78%
“…The present report provides data on effects of KRM-II-81 on nociceptive behaviors controlled by the inflammatory impact of formalin injection and on pain-related behaviors of rats undergoing chronic ligation of spinal nerves L5/6. Both models have been used to evaluate a host of other drugs that act as analgesics or are candidate molecules for pain therapeutics (Carter and Shieh, 2010;Johnson et al, 2017;Tjølsen et al, 1992;Wang and Wang, 2003).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabotropic glutamate receptors are known to modulate pain sensitivity ( Chiechio and Nicoletti, 2012 ; Palazzo et al, 2014 ; Chiechio, 2016 ). In particular analgesia can be obtained by either blocking group I mGlu receptors, namely mGlu1 and mGlu5 ( Walker et al, 2001 ; Sasikumar et al, 2010 ; Bennett et al, 2012 ; Brumfield et al, 2012 ) or by activating group II and group III mGlu receptors ( Chiechio and Nicoletti, 2012 ; Chiechio, 2016 ; Johnson et al, 2017 ). Also, we have demonstrated that epigenetic drugs that increase the expression of mGlu2 receptors are analgesic in models of persistent pain ( Chiechio et al, 2002 , 2009 , 2010 ; Zammataro et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a model of persistent colonic hypersensitivity induced colonic anaphylaxis, hypersensitivity was demonstrated as increased synaptic facilitation in the anterior cingulate from the thalamus, which was inhibited by local infusion of an antagonist targeting the NR2B subunit of NMDA receptors (Wang et al, 2015 ). In mice, a prodrug of a mGlu2/3 agonist dose-dependently reduced basal colonic sensitivity, inflammation-induced colonic hypersensitivity, and total writhing behaviors (Johnson et al, 2017 ). Intrathecal administration of suberoylanilide hydroxamic acid, a histone deacetylase inhibitor, at L6-S2 reversed swim stress-induced colonic hypersensitivity thorough changes in mGlu2/3 receptor expression in female rats (Cao et al, 2016 ).…”
Section: Neurotransmitters In Stress Pathways That Modulate Visceral mentioning
confidence: 99%